Nutritional values and varietal characteristics of two Moringa oleifera Lam. morphotypes from Chad (Global Journal of Medical Research, 2025)
Abstract- This study aims to compare the nutritional value of leaf powder from two morphotypes of Moringa oleifera Lam from Chad In 2024 at Kolobo in the Mayo Kebbi Province in southern Chad fresh leaf samples were collected from a large-leaf morphotype 1 of Moringa oleifera Lam the small-leaf morphotype 2 having been analyzed at CRSBAN in a previous study The freshly harvested leaves were transported by us sorted washed and dried in the shade The powders prepared from the dried leaves were analyzed using standard methods Physico-chemical analyses revealed that leaf powder from the small-leaf morphotype 2 is rich in protein 24 28 0 22 g 100g certain minerals mg 100g such as Ca 1443 90 11 03 Mg 176 72 0 73 Fe 53 75 5 07 Zn 17 58 0 89 and vitamins -carotene 624 40 0 41 g ER Vitamin C 65 88 0 00 mg 100g The leaf powder has a low lipids and total sugars content respectively 7 42 1 56 g 100g and 22 46 2 02 g 100g Dried Moringa oleifera broadleaf powder has a low protein content 6 09 0 15 g 100g
Keywords: Moringa; comparative study; nutritional value; morphotypes; chad